PENGARUH PROSEDUR, FEE DAN PROFESIONALISME AUDIT TERHADAP KUALITAS AUDIT DENGAN REMOTE AUDIT SEBAGAI VARIABEL MODERASI STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI JAKARTA SELATAN - Risdiana, Dina; Asmanah, Siti; Hakim, Luqman (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
This study aims to determine Procedures, Audit Fees and Professionalism on Audit Quality with Remote Audit Moderating Variables (Study at Public Accounting Firm in South Jakarta). This research method is included in quantitative research with the type of primary data source and uses attribution theory and positive accounting theory. The population in this study were public accounting firms in the South Jakarta area and the samples in this study were partners, supervisors, managers and seniors who worked at public accounting firms in the South Jakarta area. The number of samples in this study were 92 respondents. Data analysis in this study used the SmartPLS (Partial Least Square) Version 4.0 data analysis method. Procedures have a significant effect on audit quality, audit fees have a significant effect on audit quality, and professionalism has a significant effect on audit quality. Meanwhile, remote audit has no significant effect on moderating the relationship between procedures and audit quality, remote audit is unable to moderate the relationship between audit fees and audit quality. In addition, remote audit is able to moderate the relationship between professionalism and audit quality.